2020
DOI: 10.3390/v12020178
|View full text |Cite
|
Sign up to set email alerts
|

The Serological Prevalence of Rabies Virus-Neutralizing Antibodies in the Bat Population on the Caribbean Island of Trinidad

Abstract: Rabies virus (RABV) is the only lyssavirus known to be present within the Caribbean. The island of Trinidad, is richly diverse in chiropteran fauna and endemic for bat-transmitted rabies with low RABV isolation rates observed in this population. We aimed to determine the seroprevalence of rabies virus neutralizing antibodies (RVNA) in light of spatio-temporal and bat demographic factors to infer the extent of natural exposure to RABV in the Trinidadian bat population. RVNA titers were determined by the RABV mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 65 publications
(110 reference statements)
0
12
0
Order By: Relevance
“…Urban areas were also more likely to contain seropositive bats than more rural regions. Moreover, despite the presence of neutralizing antibodies (titers ranging from 10 to 1900), these bats did not display signs of disease [15], indicating that unlike the experimental infection experiments using the murine CVS-24-N2c strain, the infection was not lethal to these wild bats. Studies have shown, notably, that RABV strains of bat origin tend to be less pathogenic in mice than strains from other reservoirs, indicating an adaptation of the virus to its host [29].…”
Section: Rabies Virusmentioning
confidence: 88%
See 3 more Smart Citations
“…Urban areas were also more likely to contain seropositive bats than more rural regions. Moreover, despite the presence of neutralizing antibodies (titers ranging from 10 to 1900), these bats did not display signs of disease [15], indicating that unlike the experimental infection experiments using the murine CVS-24-N2c strain, the infection was not lethal to these wild bats. Studies have shown, notably, that RABV strains of bat origin tend to be less pathogenic in mice than strains from other reservoirs, indicating an adaptation of the virus to its host [29].…”
Section: Rabies Virusmentioning
confidence: 88%
“…Consistent with its ability to infect a wide range of animals, the virus circulates in many other Artibeus species, including the flat-faced fruit bat and great fruit-eating bat. Artibeus bat colonies in Grenada are therefore believed to be reservoirs of RABV [13][14][15][16].…”
Section: Rabies Virusmentioning
confidence: 99%
See 2 more Smart Citations
“…These are of particular concern, as they both are heavily populated, large islands that currently conduct limited active or passive rabies surveillance in bats. These are also the most densely human-populated islands, and studies elsewhere in the Caribbean have shown that urbanization level may be positively associated with rabies seroprevalence in bats [11]. The two lowest ranking island nations are the Bahamas (RV = 1.57) and Turks and Caicos Islands (RV = 1.57).…”
Section: Island-specifc Riskmentioning
confidence: 99%